Clinical Effect of Cardiac Shock Wave Therapy on Myocardial Ischemia in Patients With Ischemic Heart Failure. (July 2016) - Wang, Wenxia; Liu, Hua; Song, Mengxian; Fang, Weiyi; Yuan, Fang
Background: Cardiac shock wave therapy (CSWT) can improve myocardial ischemia and cardiac function in patients with coronary artery disease and refractory angina. The aim of the study was to test its potential role to relieve symptoms in patients with ischemic heart failure (HF) and to identify CSWT-affected genes. Methods: Cardiac shock wave therapy was performed on 23 patients (mean age: 67 ± 6 years) with ischemic HF 3 times per week for 3 weeks. Clinical assessment parameters were measured for all patients, and peripheral blood mononuclear cells (PBMCs) were isolated from whole blood of all patients 3 days before CSWT and 1 week after the 3-week CSWT schedule. RNA sequencing of PBMCs collected from 3 patients before and after CSWT was performed on the Illumina Genome Analyzer. Gene expression was determined by quantitative reverse transcription–polymerase chain reaction. Results: Cardiac shock wave therapy significantly attenuated myocardial ischemia and severity of angina, health-related quality of life, and myocardial blood flow as estimated by New York Heart Association class, Canadian Cardiovascular Society classification, Seattle Angina Questionnaire, and single photon emission computed tomography images, respectively. We then tried to investigate how CSWT improved myocardial ischemia by RNA sequencing on PBMCs. Gene set enrichment analysis on the sequencing data revealed that CSWT treatment was positively correlated with cytokine and cytokine receptor interaction and chemokine signaling pathway. Furthermore, we demonstrated that CSWT resulted in a significant increase in the expression of promoters of neovascularization (vascular endothelial growth factor A [VEGF-A], VEGF-B, chemokine (C-X-C motif) ligand 1 [CXCL1], CXCL2, CXCL3 and TNFRSF12A) and a notable decrease in the expression of a mediator of cell apoptosis (mitogen-activated protein kinase 9). Conclusions: Cardiac shock wave therapy can improve myocardial ischemia and represents as a treatment option for patients with ischemic HF through promoting neovascularization and inhibiting cell apoptosis.